A review of multi-energy hybrid power system for ships. (October 2020) - Yuan, Yupeng; Wang, Jixiang; Yan, Xinping; Shen, Boyang; Long, Teng
Abstract: In the face of increasingly severe energy shortage and environmental pollution, the use of new forms of energy will become an important direction for the future development of ships. A hybrid power system comprised of various types of energy, such as conventional fossil fuels, renewables, hydrogens, fuel cells and batteries, can ensure a continuous and reliable power source for ships by using different types of energy for various operating conditions. This has become an emerging solution for greener ships and attracted attention from both industry and academia. A state-of-the-art multi-energy hybrid power system for ships is introduced in this paper. The configuration and characteristics of series, parallel and series-parallel hybrid power systems are analyzed and compared. Challenges of multi-energy power system for large-scale ships such as reliability, control and efficiency are discussed, and possible solutions are proposed. Highlights: Development of multi-energy hybrid power system, consisting of solar energy, energy storage, and diesel engines. Key technologies to develop the multi-energy hybrid power system for ships. Issues in the large-scale multi-energy ships, and suggestions to resolve these issues.